Correlating Clinical Risk Factors and Histological Features in Ruptured and Unruptured Human Intracranial Aneurysms: The Swiss AneuX Study. Issue 7 (23rd April 2018) - Morel, Sandrine; Diagbouga, Mannekomba R; Dupuy, Nicolas; Sutter, Esther; Braunersreuther, Vincent; Pelli, Graziano; Corniola, Marco; Gondar, Renato; Jägersberg, Max; Isidor, Nathalie; Schaller, Karl; Bochaton-Piallat, Marie-Luce; et al.
Abstract: Pathogenesis of intracranial aneurysm is complex and the precise biomechanical processes leading to their rupture are uncertain. The goal of our study was to characterize the aneurysmal wall histologically and to correlate histological characteristics with clinical and radiological factors used to estimate the risk of rupture. A new biobank of aneurysm domes resected at the Geneva University Hospitals (Switzerland) was used. Histological analysis revealed that unruptured aneurysms have a higher smooth muscle cell (SMC) content and a lower macrophage content than ruptured domes. These differences were associated with more collagen in unruptured samples, whereas the elastin content was not affected. Collagen content and type distribution were different between thick and thin walls of unruptured aneurysms. Classification of aneurysm domes based on histological characteristics showed that unruptured samples present organized wall rich in endothelial and SMCs compared with ruptured samples. Finally, aneurysm wall composition was altered in unruptured domes of patients presenting specific clinical factors used to predict rupture such as large dome diameter, dome irregularities, and smoking. Our study shows that the wall of aneurysm suspected to be at risk for rupture undergoes structural alterations relatively well associated with clinical and radiological factors currently used to predict this risk.